Perlindungan Hukum Bagi Pengguna Jasa Penerbangan di Tengah Pandemi Covid-19 - Patricya Wedha Hutapea (Jurist-Diction, 2021)
AbstractThe COVID-19 pandemic has caused passenger demand to drop drastically as a result of travel restrictions and passengers' distrust of flying. However, this does not mean that passengers will not be traveling by plane during a pandemic. Passengers can be at risk of experiencing losses, one of which is the result of errors or negligence on the part of the airline company during the COVID-19 pandemic. Losses that can be suffered by passengers during the COVID-19 pandemic, such as flight delays cancellation of flights, denied boarding passengers, bodily injuries, and even death. For this reason, it is necessary to have legal protection for airline passengers to protect the rights of passengers so that health, security and safety of passengers are guaranteed during the COVID-19 pandemic. Keywords: COVID-19; Airline Liability; Flight Compensation.AbstrakPandemi COVID-19 menyebabkan permintaan penumpang menurun secara drastis sebagai akibat dari pembatasan perjalanan dan ketidakpercayaan penumpang untuk melakukan penerbangan. Akan tetapi, hal ini bukan berarti tidak ada penumpang yang melakukan perjalanannya dengan pesawat dalam masa pandemi. Penumpang dapat beresiko mengalami kerugian yang salah satunya merupakan akibat dari adanya kesalahan atau kelalaian dari pihak perusahaan maskapai di masa pandemi COVID-19. Kerugian yang dapat diderita penumpang dalam masa pandemi COVID-19 seperti keterlambatan penerbangan (delay), pembatalan penerbangan (cancellation of flight), denied boarding passenger, bodily injury, hingga kematian. Untuk itu perlu adanya perlindungan hukum bagi penumpang pesawat untuk melindungi hak penumpang sehingga kesehatan, keamanan, dan keselamatan penumpang terjamin dalam masa pandemi COVID-19.Kata Kunci: COVID-19; Tanggung Gugat Perusahaan Maskapai; Ganti Rugi Penerbangan.